Exploring Ethnomathematics in Jala Siddhi Amerta Temple - Rizkyta Zahra Prahesti; Rini Setianingsih (MATHEdunesa, 2026)
Mathematics is one of the sciences that emerged from culture, so mathematics and culture cannot be separated. Ethnomathematics is a field that combines mathematical concepts with the cultural aspects of society. Therefore, this study aims to describe the results of an exploration of Sidoarjo cultural ethnomathematics activities at Pura Jala Siddhi Amerta, focusing on six basic mathematical activities within the culture. This study employs a qualitative approach, utilizing an ethnographic method. The data obtained were collected through interviews and observations conducted by researchers with one of the administrators of Pura Jala Siddhi Amerta, using research instruments in the form of interview guidelines, observation sheets, and field notes. Then, the data will be analyzed using data analysis techniques of data reduction, data presentation, and conclusion drawing. The results showed that the form of ethnomathematics in Pura Jala Siddhi Amerta is related to the concept of number, geometric transformation, quadrilateral pyramid, and measurement. Therefore, it is hoped that teachers can use Pura Jala Siddhi Amerta as a bridge to teach math concepts, enabling students to understand the material more easily.